PENGARUH BUDAYA ORGANISASI DAN TOTAL QUALITY MANAGEMENT TERHADAP KINERJA KERJA - Cynthia Adam; Rolland E Fanggidae; Herly M Oematan (Universitas Nusa Cendana, 2019)
In this developing era of globalization, every organization needs to talk about qualities, service andperformance, especially with the job that producing goods and service. The effort to keep andincrease quality must be based on the organization’s purpose to create inovation of new goods orservice with optimal value added and reduce production with more efficient work system. Thoseeffort will increase earnings of the organization and increase their work performance. The cultureorganization has so many influence to organization’s management quality and their workperformance. One of the way that has used to achieve and upgrade their quality with perfomancetotal quality management in their company. The purpose of this research are to figure out theinfluence of organization culture and total quality management against work performance.Thiskind of research is quantity research with a descriptive approach.Sample determination byinsidental method. Insidental sampling method form a sample determination technique by accidentor insidentally match with researcher that could use as as sample. This research’s result showingthat H1 has no significant effect (tcount = 0,254 < ttable = 2,034) because the employee hard to put adifference between the organization culture and total quality management, H2(tcount = 4,367 > ttable= 2,034) and Y has a significant effect(Fcount= 10.938 > Ftable= 3,28).The conclusion of this researchare the culture organization has no significant effect on work performance, total qualitymanagement has a positive significant effect on work performance, and culture organization andtotal quality management simultanously has a positive significant effect on work performance. Keywords: Culture Organization, Total Quality Management, Work Performance